Люблю, убью, умру: [роман] / Татьяна Тронина - Тронина Татьяна Михайловна (Нити любви, 2019)
Экземпляры: Нефтебазинская библиотека (20220614) / Инвентарный номер: 15974 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 73 / ББК: 84(2Рос=Рус)6-4